MOTHER AND CHILD NUTRITION IN THE NWFP - Zaman, Haider (Journal of Ayub Medical College Abbottabad, 1991)
An analysis of food production capacity in Pakistan shows that sufficient food is available in the country. In addition, infectious diseases are on a decline, and educational and other services are reaching more and more people. Inspite of that, malnutrition persists throughout the country at high social and economic cost to the nation. Malnutrition can be defined as a state of human body which results from disease factors or from inadequate intake of nutrients, that affect digestion, absorption, transport and utilization of nutrients. This can be traced to internal as well as external factors. Internal factors are physiological in nature, which are usually caused by infectious diseases leading to pathological conditions. External factors on the other hand, are economic, social, political and cultural in nature which can influence the process of production and distribution in the society. Keeping in view the complex nature of the problem of malnutrition globally, freedom from hunger and malnutrition was declared a basic human right in the Universal Declaration of Human Rights1 in 1948. The importance of this right was reiterated in the United Nations World Food Conference2 in 1974, and elimination of hunger and malnutrition was adopted as one of the goals of the Third Development Decade. The concerns expressed at the global level adequately signify the gravity of the problem, to alleviate which actions must be initiated at the national level.